2012
DOI: 10.1007/s12298-012-0132-8
|View full text |Cite
|
Sign up to set email alerts
|

An improved plant regeneration and Agrobacterium - mediated transformation of red pepper (Capsicum annuum L.)

Abstract: Capsicum annuum (red pepper) is an important spice cum vegetable crop in tropical and subtropical countries. Here, we report an effective and reproducible auxin free regeneration method for six different red pepper cultivars (ACA-10, Kashi Anmol, LCA-235, PBC-535, Pusa Jwala and Supper) using hypocotyl explants and an efficient Agrobacterium-mediated transformation protocol. The explants (hypocotyls, cotyledonary leaves and leaf discs) collected from axenic seedlings of six red pepper cultivars were cultured o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…According to Chen (2013), the multiplication index could increase to 16.4 when GA3 was added into MS medium. In the process of shoot elongation and strengthening culture, increasing gibberellins and reducing cytokinins would be helpful for shoot growth, which is in accordance with results obtained from other plant species including Acca sellowiana (Berg) Burret (CangahualaInocente et al, 2007), Capsicum annuum L. (Kumar et al, 2012), and Mytilaria laosensis Lecomte (Qiu et al, 2013). Culture of strong and healthy shoots is the key step for plant rooting.…”
Section: Discussionsupporting
confidence: 81%
“…According to Chen (2013), the multiplication index could increase to 16.4 when GA3 was added into MS medium. In the process of shoot elongation and strengthening culture, increasing gibberellins and reducing cytokinins would be helpful for shoot growth, which is in accordance with results obtained from other plant species including Acca sellowiana (Berg) Burret (CangahualaInocente et al, 2007), Capsicum annuum L. (Kumar et al, 2012), and Mytilaria laosensis Lecomte (Qiu et al, 2013). Culture of strong and healthy shoots is the key step for plant rooting.…”
Section: Discussionsupporting
confidence: 81%
“…Optimum root induction was reported by Kim et al, (2008) by sub-culturing the capsicum shoots on MS medium with NAA 0.3 mg/l. Kumar et al, (2012) observed 100% rooting when elongated shoots were transferred to MS medium supplemented with NAA at 0.5mg/l. Rooting of the chilli shoots were the highest in MS medium with 2 mg/l IBA compared to other hormones (Manamohan et al, 2016).…”
Section: Resultsmentioning
confidence: 96%
“…Valadez et al, (2009) developed separate in vitro regeneration protocol for four different chilli genotypes. Kumar et al, (2012) The better regeneration was observed in chilli genotype G4 compared to LCA334 from cotyledonary and hypocotyl explants on MS medium supplemented with 0.25 mg/l zeatin and 2 mg/l phenyl acetic acid (PAA). Among the explants, cotyledonary leaf exhibited a higher regeneration response compared to that of hypocotyls (Manamohan et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Kumar and Tata (2010) obtained better in vitro plant regeneration from variety X-235. Kumar et al, (2012) studied regeneration of red pepper cultivars and observed variable degree of regeneration. Marta and Pawel (2015) observed organogenesis in the 3 genotypes representing C. annuum L. was similar and considerably lower for line SF9 derived from an interspecific hybrid (C. frutescens L. × C. annuum).…”
Section: Resultsmentioning
confidence: 99%